Evaluation of Lipid Profile in Adolescents - Cunha,Eduardo del Bosco Brunetti (2018)
Abstract Background: Atherosclerosis is a chronic, multifactorial and insidious disease that can begin in childhood and adolescence, and whose major consequences appear during adulthood. Serum levels of lipoproteins, such as LDL-c, total cholesterol (TC), HDL-c, and non-HDL-c can be used as a screening method for disease diagnosis. In Brazil, few studies have correlated the serum levels of those lipoproteins with age. Objective: To evaluate the serum concentrations of TC, LDL-c, HDL-c, VLDL-c, non-HDL-c and triglycerides (TG) of adolescents aged 10 to 19 years in the municipality of Araucária, Paraná state. Methods: Cross-sectional retrospective study, collecting the following data from 600 adolescents: age, sex and serum levels of TC, LDL-c, HDL-c and TG from June to December 2016. Data were analyzed using the SPSS software 2.0, with Mann-Whitney U test and Spearman coefficient of correlation to identify statistical significance (p < 0.05). Results: The female sex showed higher serum levels of TC, TG and LDL-c than the male sex. The HDL-c levels were identical in both sexes, with 48% of desirable values and 52% of low values. This study identified a strong correlation between the lipids and association with the age group of 10 to 14 years. Conclusion: Non-HDL-c showed stronger correlation with the other lipids (TG, LDL-c and TC) as compared to LDL-c, suggesting that non-HDL-c can be used as an effective complementary diagnostic method to assess the risks for atherosclerosis in adolescents.